PELAKSANAAN PEMBAYARAN KLAIM PADA PRODUK ASURANSI BERKAITAN (UNIT LINK ASSURANCE) ANTARA ASURANSI JIWA, PROTEKSI DAN INVESTASI (Studi Pada PT. Prudential Life Assurance Denpasar) - Agustawan Sidauruk, Pondang; Dunia, Ngakan Ketut; Sukranatha, A. A. Ketut (Kertha Semaya : Journal Ilmu Hukum, 2013)
With reference to the decree of Finance Minister No. 135/PMK.05/2005 about assurance companies, the assurance companies in Indonesia, in this present time, are getting increase in launching linked assurance products, one of which is PT. Prudential Life Assurance. Accordingly, the following problems arise: how to determine the amount of claims and what the obstacles are faced in determining such claims. The research method used is legal research of empirical juridical; the approach used is legislation approach and the implementation of the link assurance practices in PT. Prudential Life Denpasar. Furthermore, life assurance policy means that financially the endured people have protected themselves and their families from unexpected events and difficulties, such as disability, job loss, or the death of beloved people; therefore, there is no need for the endured people for too worrying of such risks.
Keywords: Customers, Unit Linked Assurance and Accidents/Disasters